Effect of Rapamycin Microspheres in Sjögren Syndrome Dry Eye: Preparation and Outcomes. (17th November 2019) - Wang, Shasha; Wang, Meng; Liu, Yan; Hu, Daode; Gu, Lei; Fei, Xinfeng; Zhang, Jianhong
ABSTRACT: Purpose : To prepare a drug delivery system of rapamycin poly-3-hydroxybutyrate-co-3-hydroxyvalerate microspheres (RPM) and analyze its effect on the eyes of a Sjögren's syndrome mouse model. Methods : RPM was generated using a solvent evaporation method, and observed under light and electron microscopy. No obesity diabetes (NOD) mice with Sjögren's syndrome were randomized into normal saline, empty microspheres, and RPM groups, with healthy Kunming mice as the controls. Dry eye signs were assessed using a slit lamp. Tear secretion, corneal fluorescein, keratoconjunctival rose bengal, and conjunctival impression cytology were recorded. Results : RPM was smooth and spherical, about 20–50 μm in diameter, without agglomeration or adhesion. Mice receiving RPM secreted more tears. And they had a normal corneal histology, exhibiting reduced corneal fluorescein, rose bengal staining, and conjunctival impression cytology. Conclusion : RPM improved the signs of dry eyes, improved tear secretion, decreased corneal endothelial cell injury, and improved histological damage of the cornea in NOD mice.